Touristic instrumentalization of cultural landscape. The case of Santo Stefano di Sessanio, Italy - Lopes de Oliveira, William (2023)
This article aims at to analyze the process of resignification of the cultural landscape of the Italian municipality of Santo Stefano di Sessanio, between 1999 and 2014. After a background of both economic and demographic decline started at the late of XIX century, the place has been experimenting since the beginning of the current century a set of touristic  interventions which deal for evoking the historicity of  local landscape from its morphological aspects. Among other things, this has entailed in the restoration of a group of local old buildings in order to transform them into part of a network of diffused hotels. The article is structured around sources which came from both public institutions and private groups that have intervened in the local territory. The research evinces the importance that tourism activity has been had in the municipality after the territorial abandonment context.